2013
DOI: 10.1590/s1806-37132013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Desfechos clínicos do tratamento de tuberculose utilizando o esquema básico recomendado pelo Ministério da Saúde do Brasil com comprimidos em dose fixa combinada na região metropolitana de Goiânia

Abstract: OBJECTIVE: To describe the rates of cure, treatment failure, and treatment abandonment obtained with the basic regimen recommended by the Brazilian National Ministry of Health-rifampin, isoniazid, pyrazinamide, and ethambutol for two months, followed by isoniazid and rifampin for four months-involving the use of fixed-dose combination tablets (self-administered treatment), as well as to describe adverse events and their potential impact on treatment outcomes. METHODS: This was a descriptive study based on pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 11 publications
1
22
1
11
Order By: Relevance
“…However, regarding the treatment abandonment in the sample, negative results are revealed in the study period, with the abandonment rate being higher than the 5% recommended by the MS (2) . However, the results were better than those observed in Goiânia / GO (17,5%) (8) and Recife / PE (15%) (4) . Studies on treatment abandonment point to causes associated with patient characteristics, such as being male, Lima LM, Harter J, Tomberg JO, Vieira DA, Antunes ML, Cardozo-Gonzales RI having work commitments (3) , low education and a previous record of abandonment (4) .…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…However, regarding the treatment abandonment in the sample, negative results are revealed in the study period, with the abandonment rate being higher than the 5% recommended by the MS (2) . However, the results were better than those observed in Goiânia / GO (17,5%) (8) and Recife / PE (15%) (4) . Studies on treatment abandonment point to causes associated with patient characteristics, such as being male, Lima LM, Harter J, Tomberg JO, Vieira DA, Antunes ML, Cardozo-Gonzales RI having work commitments (3) , low education and a previous record of abandonment (4) .…”
Section: Discussioncontrasting
confidence: 59%
“…Cure rates throughout the study period were higher than the 85% recommended by the MS (2) . In similar studies, lower rates were yielded, with a 75.3% cure rate in a study held in Argentina (7) , a 71% cure rate in a study conducted in Recife / PE (4) and a 67.5% cure rate in research conducted in Goiânia / GO (8) . It is considered that this result is a positive mark for the service under study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These data strongly suggest that the use of FDC tablets does not have a significant impact on adherence to treatment. Therefore, measures to improve adherence, such as supervised treatment, should not be neglected 11 . In addition, studies conducted in Brazil have demonstrated the association between lower rates of treatment abandonment and supervised treatment 39, 40, 41…”
Section: Discussionmentioning
confidence: 99%
“…Fixed-dose combinations (FDCs) of drugs for TB treatment have been advocated internationally to prevent the emergence of drug resistance attributable to inappropriate drug intake 10, 11. Use of FDCs can reduce the risk of an incorrect dosage, simplify drug procurement, and aid in ensuring adherence without changing the drug dosage.…”
Section: Introductionmentioning
confidence: 99%